Effects of acceptance and commitment group therapy on Iranian couples’ marital satisfaction in Malaysia - Hosseini, Nastaranalsadat; Lau, Poh Li; Baranovich, Diana Lea; Chan, Siaw Leng (Universiti Putra Malaysia Press, 2021)
This study investigates the effects of Acceptance and Commitment Group Therapy (ACGT) on marital satisfaction among Iranian, postgraduate married couples residing in Malaysia. The study utilised a true experimental (pretest/posttest, control group) design. Seventy-two students (36 couples) with the lowest scores from the Marital Satisfaction Inventory were randomly selected and randomly assigned into either the experimental or control group to receive either ACGT or no therapy. Subsequently, analyses of covariance (ANCOVA) showed significant differences in marital satisfaction between the experimental and control groups. The current study finds that marital satisfaction showed considerable enhancement after the ACGT, and besides, the effects of ACGT on marital satisfaction were retained after four weeks. The evaluation of the couples of the ACGT programme was also collected, which appeared to be satisfactory. This study has significant implications for marital satisfaction and counselling practice holistically.